A Numerical Investigation of Hurricane Florence‐Induced Compound Flooding in the Cape Fear Estuary Using a Dynamically Coupled Hydrological‐Ocean Model. (25th November 2022) - Bao, Daoyang; Xue, Z. George; Warner, John C.; Moulton, Melissa; Yin, Dongxiao; Hegermiller, Christie A.; Zambon, Joseph B.; He, Ruoying
Abstract: Hurricane‐induced compound flooding is a combined result of multiple processes, including overland runoff, precipitation, and storm surge. This study presents a dynamical coupling method applied at the boundary of a processes‐based hydrological model (the hydrological modeling extension package of the Weather Research and Forecasting model) and the two‐dimensional Regional Ocean Modeling System on the platform of the Coupled‐Ocean‐Atmosphere‐Wave‐Sediment Transport Modeling System. The coupled model was adapted to the Cape Fear River Basin and adjacent coastal ocean in North Carolina, United States, which suffered severe losses due to the compound flood induced by Hurricane Florence in 2018. The model's robustness was evaluated via comparison against observed water levels in the watershed, estuary, and along the coast. With a series of sensitivity experiments, the contributions from different processes to the water level variations in the estuary were untangled and quantified. Based on the temporal evolution of wind, water flux, water level, and water‐level gradient, compound flooding in the estuary was categorized into four stages: (I) swelling, (II) local‐wind‐dominated, (III) transition, and (IV) overland‐runoff‐dominated. A nonlinear effect was identified between overland runoff and water level in the estuary, which indicated the estuary could serve as a buffer for surges from the ocean side by reducing the maximum surge height. Water budget analysis indicated that water in the estuary was flushed 10 times by overland runoff within 23 days after Florence's landfall. Plain Language Summary: Compound flooding refers to a phenomenon in which two or more flooding sources occur simultaneously or subsequently within a short period of time. In this study, we present a new numerical model that combines hydrological and ocean models to represent the exchange of water levels at the land‐ocean interaction zone. To test the model's robustness, we use this model to simulate the water level changes in Cape Fear River Basin and adjacent coastal ocean in North Carolina, United States, for Hurricane Florence in 2018. The comparison between observed and simulated water level prove that the new model can better resolve the changes in water elevation during a hurricane event than the traditional method where the ocean model utilized the river model's outputs as its boundary condition. We further quantify the contributions from different processes to the water level variations in the estuary. The compound flooding in the estuary was categorized into four stages: (I) swelling, (II) local‐wind‐dominated, (III) transition and (IV) overland‐runoff‐dominated. The estuary could serve as a buffer for surges from the ocean side by reducing the maximum surge height. The water in the estuary was flushed 10 times by overland runoff within 23 days after Florence's landfall. Key Points: A coupled hydrological‐ocean model was developed using hydrological modeling extension package of the Weather Research and Forecasting model (WRF‐Hydro) and two‐dimensional Regional Ocean Modeling System (ROMS 2D) through the Coupled‐Ocean‐Atmosphere‐Wave‐Sediment Transport modeling system The dynamical coupling method was applied to the interface boundary of WRF‐Hydro and ROMS 2D to realize a seamless model coupling Hurricane Florence‐induced compound flooding event was investigated by analyzing the modeled water level evolution, water budget, and nonlinear effects in the Cape Fear Estuary